Supplementation of graded levels of rumen-protected choline to a pelleted total mixed ration did not improve the growth and slaughter performance of fattening lambs - Huo, Qin; Sun, Xuezhao; Wu, Tingting; Li, Zelin; Jonker, Arjan; You, Peihua; Li, Rongquan; Li, Jianping; Tian, Wannian; Li, Changsheng; Wang, Chunqing; He, Yuhua; et al. (Frontiers in Veterinary Science, 2022)
Choline is an essential nutrient in ruminant diets, which contributes to the fundamental biological functions of the animal. However, choline is easily degraded in the rumen before it can be absorbed. Rumen-protected choline (RPC) supplementation might support the fast growth of ruminants. This study aimed to investigate the effects of supplementing graded levels of RPC in a pelleted total mixed ration for fattening lambs. Sixty 3-month-old male Small Tail Han and northeast fine wool sheep hybrid lambs with a liveweight of 15.3 ± 1.8 kg (mean ± SD) were fed designated diets and randomly assigned into five treatment groups (n = 12 per group). The five treatments were the rate of RPC supplementation at 0, 1.25 2.50, 3.75, and 5.00 g (equivalent to 0, 0.31, 0.63, 0.94, 1.25 g of choline chloride, respectively)/kg basal diet and the RPC-supplemented feed was offered for 112 days after 12 days of adaptation. Average daily gain, dry matter intake, and nutrient digestibility were similar across treatments. The rumen pH was quadratically significant among treatments, with the lowest and highest pH observed from the 2.5 and 5 g/kg RPC supplement groups, respectively (P = 0.02). After feeding, the ruminal ammonia concentrations among treatments were different (P < 0.05), with the highest value observed from the 5 g/kg RPC supplement group. Microbial crude protein level was different, with the highest value recorded from the 0 g/kg RPC supplement group (P = 0.028). A linear effect (P < 0.05) was observed from short-chain fatty acid values among treatments before and after feeding. Serum albumin (P = 0.003) and albumin/globulin ratio (P = 0.002) had a quadratic effect, with the highest value found in the 0 g/kg RPC supplement group. Abdominal fat was higher in RPC-supplemented groups (P < 0.05) compared to the control group. Drip loss was 65% higher in RPC-supplemented groups compared to the control group (P = 0.012). Overall, the study results showed an effect of RPC on ruminal parameters, but the supplementation of low-level RPC did not improve the growth and slaughter performance of fattening lambs.